(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The article describes the role of the winter lentils to increase the fertility of old-irrigated light sierazem soils. When growing winter lentils, the microbiological activity of the studied soils increases markedly compared with the control variant.